A Categorization of Resilience: A Scoping Review - Alexander Nieuwborg; Suzanne Hiemstra-van Mastrigt; Marijke Melles; Jan Zekveld; Sicco Santema (Administrative Sciences, 2023)
The COVID-19 pandemic exposed the existential public health and economic fragilities of the civil aviation industry. To prevent future public health disruptions, the civil aviation industry is gaining interest in becoming more “resilient” but rarely elaborates on its meaning, hampering decision-making and strategy development. When looking into the academic literature it seems that a proliferation of resilience-related concepts occurred. Although enriching resilience, it also dilutes its meaning and reduces its use for practice. This paper aims to create concept clarity regarding resilience by proposing a categorization of resilience. Based upon a scoping review, this categorization dissects resilience into four reoccurring aspects: fragility, robustness, adaptation, and transformation. This categorization is expected to support sensemaking in disruptive times while assisting decision-making and strategy development on resilience. When applying this categorization in the civil aviation and public health context, the transformative aspect seems underused. Further research will focus on maturing the categorization of resilience and its use as a sensemaking tool.